2015
DOI: 10.1590/0102-33062015abb0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative wood anatomy of species of Psychotria L. (Rubiaceae) in Atlantic Rainforest remnants of Rio de Janeiro State, Brazil

Abstract: Psychotria is the largest Rubiaceae genus and one of the most abundant in the Atlantic Rainforest of Rio de Janeiro State. The present work aims to characterize and compare the wood of nine of these species. The Psychotria wood were characterized by: slightly distinct growth rings; diffuse porosity; solitary vessels or on radial multiples of 2-6 or clusters of 3-5 vessel elements, with terminal and lateral simple perforation plates and vestured and alternate intervessel and vessel-ray pits; septate fiber-trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(25 reference statements)
1
8
0
5
Order By: Relevance
“…Starch deposits, such as those observed in radial parenchyma and in the fiber-tracheids of A. pickelii, serve as a survival strategy for plants that inhabit environments with defined seasonality and species that undergo periods of stress, especially at the end of the growing season (Scatena & Scremin-Dias 2006). The presence of crystals is an important taxonomic character in Rubiaceae (Jansen et al 2001;2002;Costa et al 2006), and are found in the genera Simira (Callado & Silva Neto 2003), Bathysa (Barros et al 2008) and Psychotria (Barros & Callado 1997;Marques et al 2015). Prismatic and sand crystals were present in the wood of A. pickelli, as well as in the colleters (Tullii et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Starch deposits, such as those observed in radial parenchyma and in the fiber-tracheids of A. pickelii, serve as a survival strategy for plants that inhabit environments with defined seasonality and species that undergo periods of stress, especially at the end of the growing season (Scatena & Scremin-Dias 2006). The presence of crystals is an important taxonomic character in Rubiaceae (Jansen et al 2001;2002;Costa et al 2006), and are found in the genera Simira (Callado & Silva Neto 2003), Bathysa (Barros et al 2008) and Psychotria (Barros & Callado 1997;Marques et al 2015). Prismatic and sand crystals were present in the wood of A. pickelli, as well as in the colleters (Tullii et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It can be implied from the above account that, while empirical data on wood anatomy provided by authors such as Perrone et al 49 , Akinloye et al 51 and Marques and Callado 52 have been successfully used to diagnose many medicinal and non-medicinal plants, the story has not been the same for the three woody species reported in this study. This is a further justification for the present effort, with the results that qualitative and quantitative characteristics of wood anatomy are reliable in evaluating pharmacognostic parameters of the species.…”
Section: The Diagnostic Value Of Wood Anatomy In the Medicinal Herbs Studiedmentioning
confidence: 68%
“…O resultado obtido no tratamento controle para o comprimento de fibra, também foi verificado por Costa et al ( 2017) para madeira de Mimosa schomburgkii, em que, os mesmos encontraram valor médio de 1180 µm. Marques et al (2015) estudando as espécies de Psychotria spp. obtiveram para Psychotria deflexa um comprimento de 1170 µm demonstrando semelhança com a espécie utilizada nesse estudo.…”
Section: Discussionunclassified